2021
DOI: 10.1021/acsenergylett.1c01063
|View full text |Cite
|
Sign up to set email alerts
|

Rate Limitations in Composite Solid-State Battery Electrodes: Revealing Heterogeneity with Operando Microscopy

Abstract: Solid-state batteries (SSBs) show promise for improving energy density, cycle life, and safety. However, when active material particles are mixed with a solid electrolyte phase, the rate capability of the resulting composite electrode is often limited. As a consequence, tradeoffs between energy and power density arise, especially in thick electrodes. Herein, we fabricate graphite/Li 6 PS 5 Cl composite electrodes with varying active material fraction and thickness as model systems to probe the mechanisms that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 53 publications
2
53
0
Order By: Relevance
“…However, the magnitude of the strains in the neighboring areas increased with increasing current density. This demonstrates the impact of the early non-uniform deformations on the spatial distribution of Li plating and stripping on the solid electrolyteelectrode interface 10,21 .…”
Section: Main Textmentioning
confidence: 86%
“…However, the magnitude of the strains in the neighboring areas increased with increasing current density. This demonstrates the impact of the early non-uniform deformations on the spatial distribution of Li plating and stripping on the solid electrolyteelectrode interface 10,21 .…”
Section: Main Textmentioning
confidence: 86%
“…The morphological stability of the anode and electrochemical performance of the SSB depend on the kinetics of transport and reaction, and hence the thermal environment in the vicinity of different solid–solid interfaces within the system. Temperature-dependent mechanisms such as vacancy diffusion and viscoplasticity (creep) of lithium play a pivotal role in preserving the anode morphology during electrochemical operation. Additionally, further enhancement in ionic transport within the solid electrolyte has also been considered beneficial toward achieving homogenized reaction distributions at the anode interface and improved ionic percolation within the cathode microstructure. , …”
Section: Theoretical Advantages Of Solid-state Batteries For Fast Chargementioning
confidence: 99%
“…With an increase in active material loading to achieve higher energy densities, ion percolation limitations within the cathode architecture become more critical. In this context, recent studies have reported a decrease in rate performance at higher active material loading (∼80 wt%). ,, This has been attributed to a higher electrostatic potential (IR) drop within the composite electrode structure, which results in spatial heterogeneity in state-of-charge throughout the electrode thickness . Therefore, energy and power density trade-offs exist in composite cathodes in SSBs, analogous to Li-ion batteries.…”
Section: Challenges For Fast Charge Of Solid-state Batteriesmentioning
confidence: 99%
See 2 more Smart Citations